Trade-off between greenhouse gas emission tax and paddy production - Deepa, M P M; P S Srikantha Murthy (Agricultural Economics Research Review, 2023)
Rice cultivation is an important contributor to the greenhouse gas emissions. The rice cultivators, however, do not pay for the greenhouse gas emissions. This paper estimates the cost of greenhouse gas emissions from the perspective of imposing an emission tax, and consequently its impact on rice production. The findings show that imposing an emission tax causes a reduction in rice production and leads to an increase in its price, given the critical role of rice in India, in terms of both production and consumption. More importantly, it will adversely affect the nation’s food security. Thus, there is a need for promoting adaptation and mitigation technologies and practices to reduce the greenhouse gas emissions.